Police investigation and administration of justice in crimes against sexual freedom, Cusco-Peru - Aguilar Sánchez, Juan Mauro (2024)
The purpose was to determine the relationship between the evaluation of the police investigation and the administration of justice in crimes against sexual freedom in the 1st Unipersonal Criminal Court of the Province of Anta, Cusco, 2022. The research is basic, with correlational design, non-experimental, the sample is 45 experts, and questionnaires were used. The results reveal that 75.6% rated the police investigation at a medium level and 80.0% rated the administration of justice in crimes against sexual freedom at a medium level. The valuation of the criminal investigation and the police report showed a significant relationship with the administration of justice in crimes against sexual freedom obtaining a sig. of less than 0.050, the coefficients obtained were 0.558, 0.607 and 0.606 respectively for the dimensions and variable 2.